Electrical Properties of Carbon Nanotube-Reinforced Polymer Composites; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Lebedev S. M. Sergey Mikhailovich; Gefle O. S. Olga Semenovna; Amitov E. T. Ernar Tanirbergenuly; Predtechensky M. R.; Bezrodny A. E. (Advanced Materials and Alloys, Nanomaterials and Nanotechnology, 2016)
Title screen